2022
DOI: 10.1007/s00520-021-06708-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of resistance training during adjuvant chemotherapy and radiation therapy in cancer care: a systematic review and meta-analysis

Abstract: Purpose To determine the effect of resistance training during adjuvant chemotherapy and radiation therapy in cancer patients on measures of lean mass and muscle strength. Secondary aims were to analyse the prescription and tolerability of supervised resistance training in this population. Methods EMBASE, Medline, CINAHL, Cochrane Library and Web of Science were searched from inception until 29 March 2021. Eligible randomised controlled trials (RCTs) examining supervised resistance training > 6 weeks duration d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Moreover, substantial empirical research has demonstrated that engaging in physical activity can significantly enhance lower-body strength, upper-body strength, and lean body mass in cancer patients undergoing chemotherapy and radiotherapy interventions [ 97 , 98 ]. A randomized controlled trial was conducted to investigate the impact of resistance training on the maximal muscle strength of postmenopausal breast cancer survivors.…”
Section: Physical Exercises and Breast Cancer Post-treatmentmentioning
confidence: 99%
“…Moreover, substantial empirical research has demonstrated that engaging in physical activity can significantly enhance lower-body strength, upper-body strength, and lean body mass in cancer patients undergoing chemotherapy and radiotherapy interventions [ 97 , 98 ]. A randomized controlled trial was conducted to investigate the impact of resistance training on the maximal muscle strength of postmenopausal breast cancer survivors.…”
Section: Physical Exercises and Breast Cancer Post-treatmentmentioning
confidence: 99%
“…Many clinical trials have examined the effects of exercise during adjuvant therapy (23)(24)(25), however, few have reported on cancer outcomes (10,24,25). As one example, the Supervised Trial of Aerobic versus Resistance Training (START) (11) randomized 242 early-stage breast cancer patients initiating chemotherapy to usual care (n=82), aerobic exercise (n=78) or resistance exercise (n=82).…”
Section: Scenario #2: Actively Treated Micrometastasesmentioning
confidence: 99%
“…Therefore, cancer biology has been researched extensively to understand the mechanisms of cancer growth and metastasis, and subsequently, to develop better, effective, and safer treatment modalities. Accordingly, several novel approaches are being used clinically, or are in clinical trials, including combination chemotherapy ( Chung et al, 2020 ; Yamada et al, 2022 ), immunotherapy ( Kraehenbuehl et al, 2022 ; Li et al, 2022b ), radiation ( Tchelebi et al, 2020 ; McGovern et al, 2022 ), and photodynamic therapy ( Li et al, 2020a ; Lo et al, 2020 ). Although cancer research has advanced progressively, there are only a few notable treatment improvements ( Agostinis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%